Relevance Brand Pride and Brand Loyalty in Choosing a Hospital during Pandemic - Hani Wijaya; Muhamad Ivan; Ivansius Ivansius; Yolanda Masnita (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
One of the basic considerations that can be used is the credibility of the hospital based on brand pride and brand loyalty. However, in hospitality, it is stated that brand pride has not been proven effect on brand loyalty, especially in the hospital industry sector during the COVID-19 pandemic. Using the Grand Theory Rational Choice Theory (RCT) to validate individual behavior by involving self-esteem, digital customer review and self-regulation is believed to make a positive contribution to strengthening brand pride of hospital customers for brand loyalty during the COVID-19 pandemic. This research contributes in the form of positive input for the hospital sector to be able to provide good services during the covid 19 pandemic.